Analysis of the Contribution of Balance Funds to Total Government Revenues in Regency/Municipality in Jambi Province - Nurkodri, Moh Sahroni; Laryan, Pandu; Pasla, Bambang Niko (Jurnal Prajaiswara, 2023)
Introduction/Main Objectives: This study aims to analyze the contribution of Balance Funds to Total Regional Revenue in Regencies/Cities in Jambi Province in 2010-2021. Background Problems: How is the contribution of the Balance Fund to Total Regional Revenue in Regencies/Cities in Jambi Province in 2010-2021. Research Methods: This research uses a quantitative method using secondary data on the realization of the Balance Fund and the realization of Regional Revenue in Regencies/Cities in Jambi Province in 2010-2021. Finding/Results: Based on the results of the analysis carried out and compared with the contribution criteria, the results vary with the lowest contribution at 58.84% which occurred in 2021 in Tanjung Jabung Barat Regency and the highest contribution was 89.90% in 2010 in Sarolangun Regency. Conclusion: The contribution of Balance Funds to total Regional Revenues in Regencies/Cities in Jambi Province is still very high (> 50%) or in other words, Total Regional Revenues are still dominated by allocations from the central government.